Macropsidius bogutensis (Mityaev, 1990) species group (Hemiptera: Auchenorrhyncha: Cicadellidae: Eurymelinae: Macropsini) in Kazakhstan: taxonomy, biology, and evolution - Tishechkin, Dmitri Yu. (Zootaxa, 2022)
Illustrated descriptions of species from the Macropsidius bogutensis group from Southern Kazakhstan with data on biology, male calling signals, and distribution are provided. M. karatavicus sp. n. from Syrdaryinskiy Karatau Range is described and the synonymy M. bogutensis Mityaev, 1990 = M. zhuravlevi Mityaev, 2014, syn n. is established. Conclusions concerning the evolution of M. bogutensis species group are presented.